Changing Management Control And Practices Towards A High-Performance Culture:The Case Of A Newly Acquired Organisation In Malaysia - Abdullah, Zarifah (2011)

(untitled)
This research employs an interpretive case study method to examine how a newly acquired organisation changes its organisational culture or institutions. The study specifically looks at how the changes brought in through a culture of highperformance, introduced by the new management of a Western multinational, have become institutionalised and formed a new culture in the acquired organisation. Data was collected through semi-structured interviews, document reviews, informal conversations and observations in the case organisation. Van der Steen’s (2006) framework of institutional change is used to explain the data.